COMMUNICATION STRATEGIES OF RELIGIOUS LEADERS IN DELIVERING SOCIAL AND RELIGIOUS MESSAGES IN THE PUBLIC SPHERE OF TERNATE CITY - Athirah Rizki Salsabila; Syahrir Ibnu; Alwi Abdul Haq (Penelitian dan Pengembangan Ilmu, 2025)
This study examines the communication strategies employed by religious leaders in delivering social and religious messages within the public sphere of Ternate City. Using a phenomenological approach, it investigates how religious figures interpret and enact their communicative roles in a multicultural society. Data were obtained through field observations and in-depth interviews with interfaith religious leaders. The findings indicate that communication strategies are organized around three key dimensions: (1) a dialogical dimension that emphasizes openness, audience sensitivity, and contextual adaptation; (2) a moral–social dimension that integrates religious teachings with contemporary social issues; and (3) a digital dimension that reflects the use of social media and online platforms to extend religious and social outreach. The results further show that the communicative practices of religious leaders constitute a dynamic process of social structure reproduction, aligning with Giddens’ Structuration Theory. In this process, religious leaders act as agents who actively reinterpret and reinforce social values through communicative actions. Overall, this study contributes to public communication scholarship by offering an empirically grounded understanding of religious communication in multicultural contexts. It underscores the strategic role of religious leaders in promoting social cohesion and maintaining communal harmony in modern society.